Evaluation of the yield and agronomic trait performance of BC2F2 common bean lines at Hawassa, Ethiopia (Asian Journal of Agriculture, 2024)
Abstract. Ebrahim MS, Bisetegn KB, Tedla YR, Tufa MT. 2024. Evaluation of the yield and agronomic trait performance of BC2F2 common bean lines at Hawassa, Ethiopia. Asian J Agric 8: 50-56. The common bean is the most important legume in Ethiopia and is grown mainly for domestic consumption, export and as a source of protein. Farmers in the study area are still producing old varieties; therefore, the production decreases in the area, even though there are suitable environments for common bean production. Bean anthracnose is one of the major constraints that challenged the production of common bean in the study area. To address the above gap, to identify introgressed bean lines for anthracnose resistance with improved agronomic traits that were developed through backcross breeding program using pot experiments under screen house conditions. Twelve common bean genotypes, including eight developed BC2F2 lines, two parental lines, and two cultivars, were used to evaluate agronomic performance. Data on seven quantitative traits and three qualitative traits were collected from each tagged tested material. Analysis of variance revealed a highly significant difference (p
Keywords: Better performance, developed lines, old variety, quantitative traits